Taxonomic revision of the Neotropical species of the braconid wasp genus Pedinotus Szépligeti, 1902 (Hymenoptera: Braconidae: Doryctinae) - Belokobylskij, Sergey A.; Castro, Clóvis Sormus De; Shimbori, Eduardo Mitio; Zaldívar-Riverón, Alejandro; Penteado-Dias, Angélica Maria; Braet, Yves (Zootaxa, 2017)
A revision of the Neotropical species of the braconid wasp genus Pedinotus Szépligeti and molecular characterization of some species based on the COI mitochondrial DNA gene are provided. Twenty four new species are described: P. avispas sp. nov., P. bororo sp. nov., P. botocudo sp. nov., P. brunniventris sp. nov., P. cerdai sp. nov., P. daedalus sp. nov., P. dispar sp. nov., P. dominica sp. nov., P. elongatus sp. nov., P. glabroscutum sp. nov., P. guyanensis sp. nov., P. haliti sp. nov., P. intermedius sp. nov., P. maracas sp. nov., P. nigriceps sp. nov., P. nitidus sp. nov., P. nolli sp. nov., P. peruanus sp. nov., P. plaumanni sp. nov., P. propodealis sp. nov., P. rondoni sp. nov., P. subtristis sp. nov., P. szepligetii sp. nov., and P. trinidad sp. nov. Moreover, P .brasiliensis Szépligeti, 1902, P. columbianus Enderlein, 1912, P. ferrugineus (Enderlein, 1920), P. niger Marsh 2002, P. pardalotus Marsh 2002, P. rojasi Marsh 2002, P. tundisii Felix et Penteado-Dias, 2004 and P. variegatus Marsh 2002 are redescribed. The following new synonyms are proposed: Lamquetia Braet, Barbalho et Achterberg, 2003 under Pedinotus Szépligeti, 1902 (syn. nov.); L. marshi Braet et Barbalho, 2003 and P. fasciatus Castro, Nunes et Penteado-Dias, 2010 under P. pardalotus Marsh, 2003 (syn. nov.). The following new combination is suggested: P. rufus (Braet et van Achterberg, 2003), comb. nov. (from Lamquetia rufa). A key to the Neotropical species of Pedinotus is provided.